2000
DOI: 10.2307/1593105
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of West Nile Virus in Chickens

Abstract: In the fall of 1999, West Nile virus (WNV) was isolated for the first time in the Western Hemisphere during an outbreak of neurologic disease in humans, horses, and wild and zoo birds in the northeastern United States. Chickens are a potential reservoir for WNV, and little is known about the pathogenicity of WNV in domestic chickens. Seven-week-old chickens derived from a specific-pathogen-free flock were inoculated subcutaneously with 1.8 x 10(3) 50% tissue culture infectious dose of a crow isolate of WNV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
76
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 7 publications
13
76
0
Order By: Relevance
“…However, histopathologic lesions of encephalitis were not observed, and renal lesions were uncommon in the blue jays in this study, similar to reported findings in blue jays, crows, chickens, and turkeys (Senne et al, 2000;Swayne et al, 2001;Weingartl et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, histopathologic lesions of encephalitis were not observed, and renal lesions were uncommon in the blue jays in this study, similar to reported findings in blue jays, crows, chickens, and turkeys (Senne et al, 2000;Swayne et al, 2001;Weingartl et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Gross hemorrhage of the brain, splenomegaly, meningoencephalitis, and myocarditis were the most prominent lesions noted in birds found dead at the beginning of the WNV epidemic (Steele et al, 2000). Subsequent studies noted similar lesions in experimentally infected blue jays, crows, chickens, and turkeys, as well as naturally infected owls (Senne et al, 2000;Swayne et al, 2000;Fitzgerald et al, 2003;Weingartl et al, 2004;Wü nschmann et al, 2004). No pathognomonic lesions for WNV have been described, however, and lesions between species are not consistent.…”
Section: Introductionmentioning
confidence: 91%
“…West Nile virusneutralizing antibodies have been reported as early as 5-7 d pi in experimentally challenged chickens (Senne et al 2000;Langevin et al 2001). Endpoint PRNT titers at 14 d in the present study are comparable to those developing in chickens at 14 d (Senne et al 2000;Langevin et al 2001).…”
Section: Discussionsupporting
confidence: 73%
“…However, lesions in brain or other tissues were not observed in domestic turkeys inoculated with WNV. 15,16 The pathology of WNV and the viral tissue tropism in the turkey of this report were similar to what was found in many zoologic birds and wild birds, but not in experimentally infected domestic turkeys. 13 The levels of viremia in chickens and geese infected with WNV was sufficiently high to contribute to the transmission cycle, but the viral concentrations in domestic turkeys inoculated with WNV was insufficient to infect mosquitoes.…”
supporting
confidence: 84%